Strategic Settings in Micro and Small Business: an analysis on the performance of women entrepreneurs of services sector in Londrina - PR - Gonçalves, Gabriel Varea; Amâncio-Vieira, Saulo Fabiano; Melatti, Gerson Antonio; Gimenez, Fernando Antonio Prado; Negreiros, Letícia Fernandes de (Revista de Administração da UFSM, 2017)
This research seeks to verify the existence of different settings in the process of strategy formation in small enterprises in the service sector of Londrina/PR. Theoretical framework is based on studies of Cochia and Machado da Silva (2004) about the environmental context, Miles and Snow (1978) about four types of strategy, Carland, Carland and Hoy (1992, 1998) and Inácio and Gimenez (2004) to measure the entrepreneur index, and Bailey and Avery (1998) for the classification of strategic types. This research is classified as quantitative, descriptive and exploratory study. It was conducted a censos with the 70 service companies associated with CMEG / FECOMERCIO. The results demonstrate that most of the leaders of these companies have Entrepreneurial attitude, the main type of competitive strategy adopted was incremental, that the environmental context of companies is local, and the dominant dimension in the development of the strategy is the Prospector, in other words, companies are continually seeking to expand the range of products / services.